A comprehensive analysis of IoT security and privacy in smart city applications - Zainuddin, Ahmad Anwar; Othman , Adam; Adlin Muhammad Zahid , Nur; Anis Sofea Kamarul Zaman , Nur; Nur Maisarah Ahmad Razmi , Alin; Haiqal Azreen Kamarul Zaman , Mohammad (Association for Scientific Computing Electrical and Engineering, 2024)
With the increasing growth of smart cities, the Internet of Things (IoT) has emerged as a key enabler, integrating various systems and devices to create intelligent urban environments. However, increased interconnectedness raises significant concerns regarding security and for IoT communications privacy. This work addresses the problems with and remedies for IoT connectivity in smart cities that are related to security and privacy. The problems will be addressed by examining the potential risks and vulnerabilities associated with IoT networks, considering device authentication, data encryption, access control, and intrusion detection. Furthermore, an investigation on privacy issues and provide ways to protect sensitive data, such as differential privacy and data anonymization will be conducted. This work further provides a rundown of current safeguarding and discretion practises in IoT communications and highlight new technologies that hold promise for addressing these challenges, based on a detailed assessment of existing research and case studies. Moreover this work outlines important avenues for future study and offer suggestions for strengthening the privacy preservation of IoT communications in the context of tech cities. By solving these fundamental issues, the dependability, sustainability, and trustworthiness of IoT deployments in smart cities can be guaranteed, enabling them to reach their full potential for enhancing the quality of life for urban people.